Emerging core-shell nanostructured catalysts of transition metal encapsulated by two-dimensional carbon materials for electrochemical applications. (October 2018) - Thanh Tran, Duy; Kshetri, Tolendra; Dinh Chuong, Nguyen; Gautam, Jagadis; Van Hien, Hoa; Huu Tuan, Le; Kim, Nam Hoon; Lee, Joong Hee
Graphical abstract: Highlights: Transition metal encapsulated in carbon layers (TM@2D-carbon material) showed unique structure and properties. Recent advancement of synthesis method for various TM@2D-carbon materials was highlighted. Morphology/structure-physicochemical properties relationship of TM@2D-carbon material was discussed. The potential electrochemical applications of TM@2D-carbon material were overviewed. Abstract: Development of cost-effective, rich-reserve, and highly efficient substitutes to replace the precious metal catalysts is necessary in the field of electro-catalysis to reduce the costs and enhance the efficiency of catalysts. Although, various nonprecious metal catalysts have received much attention, some critical issues still remain in practically applied catalytic processes due to their insufficient activity and poor stability. A novel and potential approach to design catalysts based on nonprecious metal encapsulated by two-dimensional (2D) carbon supporting materials has demonstrated unique advantages in terms of enhanced catalytic activity and stability, especially under harsh operational conditions. This is due to the enriched electrochemical active sites and highly improved interaction between the components by exceptional structural design and alternation of the associated electronic properties. This review highlights the recent advancement of state-of-the-art research on the synthesis, morphology, properties, and applications of the transition metal-based catalysts encapsulated in 2D-carbon supporting material hybrids. The pros and cons of various synthesis methods are discussed in detail to understand the relationships between such unique morphology/structure and physicochemical properties for enhanced catalytic performance. In addition, their potential electrochemical applications are also emphasized, including biosensors, supercapacitors, batteries, fuel cells, and water splitting. Finally, the current challenges in fundamental research and practical applications, and forthcoming opportunities for these promising materials, are also briefly discussed.